Newcomers' stress and organizational socialization: The role of self‐efficacy, learning, and supervisors' information sharing. - Ma, Ying (Applied Psychology: An International Review, 2026)
Individuals transitioning into a new organization are often placed in a high‐anxiety situation, which can hinder their ability to quickly integrate into the organization. However, studies that directly apply a stress perspective to socialization‐related phenomena remain scarce. Based on social cognition theory, I examined how and when newcomers' task and relationship stress affect their adjustment during organizational socialization. In Study 1, I collected paired data from 259 newcomers and their direct supervisors via an online survey company for academic research. The findings showed that task self‐efficacy and task learning serially mediated the effect of newcomers' task stress on job performance and turnover intention. Relationship self‐efficacy and relationship learning serially mediate the effect of newcomers' relationship stress on social integration and turnover intention. In addition, the results supported the moderating role of supervisors' information sharing, as it weakened the effect of newcomers' stress on self‐efficacy. In Study 2, paired data from 437 newcomers and their direct supervisors were collected from three technology information companies. The analysis results largely supported the research hypotheses and further strengthened the conclusions. Theoretical contributions, practical implications, and directions for future research are discussed.